AN ANALYSIS OF IMPOLITENESS STRATEGIES IN MOBILE LEGENDS BANG BANG PLAYER ON TWITTER AT MLBBFESS FOLLOWERS - Maulana, Bahtiar; Rahmadhan, Alif; Khadifa Abdul Rozzaq Wijaya, Rahmaditya (Universitas Duta Bangsa Surakarta, 2023)
The purpose of this study is to analyze the impoliteness strategies who always used by follower twitter of @mlbbfess. This research was proposed by Culpaper’s theory. In this study, the researchers analyzed impoliteness using quantitative analysis methods. The researchers spreading a questionnaire to followers of @mlbbfess by direct message. After collecting and analysis the data, the researchers identified 11 utterances, the researchers discovers two kinds of impoliteness as a results, including 7 hearer perceives and constructs behavior as intentionally face-attack and 4 combination. The hearer perceives and constructs behavior as intentionally face-attack frequently found in the data.